Shopping Lifestyle dan Diskon terhadap Impulse Buying di E-Commerce - Putri Agustin Dwi Ningrum; Hery Pudjoprastyono (Journal of Management and Bussines (JOMB), 2023)
This study aims to analyze the effect of shopping lifestyle and discounts on impulse buying in e-commerce Shopee for UPN "Veteran" East Java students. This research method is quantitative and uses the variables "Shopping Lifestyle" (X1), "Discounts" (X2), and "Impulse Buying" (Y) as research variables. This study used a convenience sample of 70 people who were taken non-probabilistically. Information was collected by sending questionnaires to prospective respondents. Structural Equation Modeling (SEM) is a component-based data analysis technique that utilizes the Partial Least Squares (PLS) analysis tool. The results showed, a) the Shopping Lifestyle variable for Impulse Buying had a path coefficient value of 0.533508, a T-statistic value of 7.783541 > 1.96 (from the table of Zα values ​​= 0.05), and a P-Value of 0.000 < 0.050; b) the Discount variable (X2) to Impulse Buying (Y) has a path coefficient value of 0.252657, a T-statistic value of 7.783541 > 1.96 (from the Zα value table = 0.05), and a P-Value of 0.001 <0.050. In conclusion, shopping lifestyle and discounts have a statistically significant positive effect on impulse buying made at Shopee. Keywords: Discounts, Impulse Buying, Shopee, Shopping Lifestyle